Attribute exclusion strategies in airline choice: Accounting for exogenous information on decision maker processing strategies in models of discrete choice - Rose, J.; Hensher, D.; Greene, William; Washington, S. (2012)
We examine the impact of individual-specific information processing strategies (IPSs) on the inclusion/exclusion of attributes on the parameter estimates and behavioural outputs of models of discrete choice. Current practice assumes that individuals employ a homogenous IPS with regards to how they process attributes of stated choice (SC) experiments. We show how information collected exogenous of the SC experiment on whether respondents either ignored or considered each attribute may be used in the estimation process, and how such information provides outputs that are IPS segment specific. We contend that accounting the inclusion/exclusion of attributes will result in behaviourally richer population parameter estimates. © 2012 Copyright Taylor and Francis Group, LLC.